الوقف الثقافِي للمغاربةِ في مصر العثمانيةِ من خلال سجلات المحاكم الشرعيّة تجربة أهل جربة وأهل فاس في القرن 12هـ/18م - مصلح, أحمد بن مهني (جامعة ﻣﺤمد اﻟﺨامس, 2013)
Keywords: Waqf (fondations) – Djerba

المحلّي مفردا والمحلّي جمعا: دلالات عقود الوقف الوفاقية بجزيرة جربة في القرن 19م - المريمي, محمد (مجلة الناصرية للدراسات الاجتماعية والتاريخية, 2016)
Our research originated from two family archive documents located in the Tunisian island of Djerba which relate to two notarial acts. The first act concerns a jâma’ (oratory) from the wahaby community while the second relates to a mastawâ community one. Both communities are factions of the ibadhy school of thought and the aforementioned documents date back to the second half of the 19th century ie nearly one century after the island’s status switched from a traditional cheikhat status to a caïdat one due to the rising influence of the malekits within the island. Being originally perceived as « foreigners », the Malekits fully acted from then on as local actors while showing objective alliance to the power in Tunis. Besides, other sources have revealed that some ibadhy families intentionally converted to malekism choosing to abandon irreversibly their original religious thought starting from the 18th century. Our research focuses on compromise as a way of resistance for natives’ forces against the Malekit surrounding environment as it became their established neighbour. We first study the corpus provided by our sources featuring the ibadhy traditions as well as malekit school fiqh. We try then to draw the relationship this corpus has with the local and locality establishments. Our aim was to follow the move from an established single mainstream local community (ibadhy) to a pluralist local landscape (ibadhy-malekit). Finally one power opposing the compromise shapes up on legal grounds. In fact, the agreement approved by both the malekit cadi and the mastâwâ ibadits went unnoticed without any objection. The one agreed with the wahbits has on the other hand raised many reservations. The fuqahâ-s of Tunis answering one question from an anonymous person signaled a mistake in the drafting of the notarial act in question and concluded it was invalid and thus could not be acceptable as evidence. As such, a frontier was being marked out between a pluralist local and a unitarian global.
Keywords: Djerba – Empire ottoman; Waqf (fondations) – Djerba

أهل جزيرة جربة من خلال أوقاف الأباضية وهكداش بيعة الغريبة اليهودية - المريمي, محمد (مركز النشر الجامعي‏, 2018)
Keywords: Djerba – Empire ottoman; Ibadisme – Djerba; Judaïsme – Djerba; Waqf (fondations) – Djerba